Identification and enhancing production of a novel macrolide compound in engineered Streptomyces peucetius. Issue 5 (14th January 2021) - Pham, Van Thuy Thi; Nguyen, Hue Thi; Nguyen, Chung Thanh; Choi, Ye Seul; Dhakal, Dipesh; Kim, Tae-Su; Jung, Hye Jin; Yamaguchi, Tokutaro; Sohng, Jae Kyung
Abstract : Activation of peucemycin in S. peucetius DM07 by the OSMAC strategy. Abstract : Streptomyces peucetius produces doxorubicin and daunorubicin, which are important anticancer drugs. In this study, we activate peucemycin, a new antibacterial compound, using an OSMAC strategy. In general, bioactive compounds are produced in a higher amount at room temperature; however, in this study, we have demonstrated that a bioactive novel compound was successfully activated at a low temperature (18 °C) in S. peucetius DM07. Through LC-MS/MS, IR spectroscopy, and NMR analysis, we identified the structure of this compound as a γ-pyrone macrolide. This compound was found to be novel, thus named peucemycin. It is an unusual 14-membered macrocyclic γ-pyrone ring with cyclization. Also, peucemycin exhibits potential antibacterial activity and a suppressive effect on the viability of various cancer cell lines.